Understanding and Applying Chelated Fertilizers Effectively Based on Soil pH - Guodong Liu; Edward Hanlon; Yuncong Li (EDIS, 2012)
Plant nutrients are one of the environmental factors essential for crop growth and development. Nutrient management is crucial for optimal productivity in commercial crop production. Those nutrients in concentrations of  ≤ 100 parts per million (ppm) in plant tissues are described as micronutrients and include iron (Fe), zinc (Zn), manganese (Mn), copper (Cu), boron (B), chlorine (Cl), molybdenum (Mo), and nickel (Ni). Micronutrients such as Fe, Mn, Zn, and Cu are easily oxidized or precipitated in soil, and their utilization is, therefore, not very efficient. Chelated fertilizers have been developed to increase micronutrient utilization efficiency. This 7-page fact sheet provides an overview of chelated fertilizers and considerations for their use to county Extension faculty, growers, and students who are interested in commercial crop production. Written by Guodong Liu, Edward Hanlon, and Yuncong Li, and published by the UF Department of Horticultural Sciences, November 2012.